Transcriptional downregulation of FAM3C/ILEI in the Alzheimer's brain. Issue 1 (10th August 2021) - Watanabe, Naoki; Nakano, Masaki; Mitsuishi, Yachiyo; Hara, Norikazu; Mano, Tatsuo; Iwata, Atsushi; Murayama, Shigeo; Suzuki, Toshiharu; Ikeuchi, Takeshi; Nishimura, Masaki
Abstract: Amyloid-β (Aβ) accumulation in the brain triggers the pathogenic cascade for Alzheimer's disease (AD) development. The secretory protein FAM3C (also named ILEI) is a candidate for an endogenous suppressor of Aβ production. In this study, we found that FAM3C expression was transcriptionally downregulated in the AD brain. To determine the transcriptional mechanism of the human FAM3C gene, we delineated the minimal 5′-flanking sequence required for basal promoter activity. From a database search for DNA-binding motifs, expression analysis using cultured cells, and promoter DNA-binding assays, we identified SP1 and EBF1 as candidate basal transcription factors for FAM3C, and found that SMAD1 was a putative inducible transcription factor and KLF6 was a transcription repressor for FAM3C . Genomic deletion of the basal promoter sequence from HEK293 and Neuro-2a cells markedly reduced endogenous expression of FAM3C and abrogated SP1- or EBF1-mediated induction of FAM3C. Nuclear protein extracts from AD brains contained lower levels of SP1 and EBF1 than did those from control brains, although the relative mRNA levels of these factors did not differ significantly between the groups. Additionally, the ability of nuclear SP1 and EBF1 in AD brains to bind with the basal promoter sequence-containing DNA probe was reduced compared with the binding ability of these factors in control brains. Thus, the transcriptional downregulation of FAM3C in the AD brain is attributable to the reduced nuclear levels and genomic DNA binding of SP1 and EBF1. An expressional decline in FAM3C may be a risk factor for Aβ accumulation and eventually AD development.